Radicalizing Religion? Religious Identity and Settlers' Behavior. (2nd June 2016) - Hirsch-Hoefler, Sivan; Canetti, Daphna; Eiran, Ehud
ABSTRACT: Does religious identity prompt radical action? This article presents a model of individual-level radical action. Drawing mostly on collective action theory the article posits that organizational membership drives the effect of religious identity on individual-level radical action. Using survey data the article assesses the behavior of Jewish settlers in the West Bank in the face of the 2005 Gaza withdrawal. The article finds that contra the prevailing view, which holds that religious identity alone is sufficient to trigger violence, evidence suggests that organizational membership is a mechanism bridging religious identity and radical action. Longstanding arguments tying radical actions solely to religion may require substantial revision.